Phosphorylated polysaccharides derived from Scrophulariae Radix mitigates lipopolysaccharide (LPS)-induced acute lung injury in mice by suppressing the NF-κB-mediated inflammatory response - Lufen Huang; Anguo Wu; Jiaxue Chen; Jiamin Zhu; Xulong Qin; Jianing Mi; Bowen Wei; Jianan Wang; Yufeng Liu (Food and Agricultural Immunology)
Acute lung injury (ALI) is a severe form of diffuse lung disease that poses a significant health burden in clinical settings. Numerous natural compounds derived from plants have shown effective anti-inflammatory activities with low toxicity, particularly polysaccharides, which have garnered considerable attention. This study explores key aspects of the pathogenesis of ALI and the potential mitigation effects of phosphorylated polysaccharides derived from Scrophulariae Radix (PPSR) in a lipopolysaccharide (LPS)-induced mouse model of ALI. These include alterations in the lung tissue wet/dry ratio, histopathological changes, modulation of pro-inflammatory cytokines, and inhibition of the NF-κB signalling pathway. Moreover, PPSR significantly reduced lung nitric oxide (NO) production and the expression of inducible NO synthase (iNOS) in lung tissue. The findings provide important insights into the mechanisms underlying the therapeutic effects of PPSR, emphasising its anti-inflammatory properties and its potential to alleviate the detrimental consequences of ALI.